Environmental and energy assessment of a family house - Turcsanyi, Peter; Sedlakova, Anna; Kridlova Burdova, Eva; Vilcekova, Silvia (International Conference “Environmental Engineering”, 2017)
Term energy efficient building is well know from year 1991, when Austrian physicist Dr. Feist designed and built first passive house, using current physical and practical knowledge. In the next 25 years buildings using principles of energy efficient design have changed dramatically. In a good way. It is mandatory for Slovak Republic as a part of European Union to act according European parliament directives. One of directives concerns lowering total energy consumption and emissions in the building sector – Directive 2010/31/EU on Energy performance of buildings, also known as Directive “20-20-20”. According to this directive, Slovak Republic has agreed to lower total energy consumption in building industry by 20% until year 2020. Plan on lowering total energy consumption has affected creation of new – technical and energy efficient building materials with emphasis on environmental load. It this paper, ultra-low-energy family house located in Košice, Slovakia was assessed from environmental and energy point of view. With help on modern diagnostic methods and thermo-physical simulation software DesignBuilder, we will virtually evaluate energy need of house throughout the reference year, and indoor quality from the environmental point of view, such as CO2 levels and bounded energy using LCA method.
Keywords: LCA method; ultra-low-energy house; energy load; heating and cooling